Hospital and Patient Characteristics Associated with Neonatal Blood Stream Infection in Inpatient Care: Insights from the 2019 HCUP KID Database - Michael Samawi; Gulzar H. Shah; Linda Kimsey; Kristie C. Waterfield; Susan Hendrix (MDPI AG, 2024)
Background: This study explores the associations between pediatric adverse events (PAEs) and both hospital and patient characteristics within the inpatient hospital setting, specifically focusing on Neonatal Blood Stream Infection (NBSI) as defined by pediatric quality indicators (PDIs) from the Agency for Healthcare Research and Quality (AHRQ). This research aims to answer questions regarding the relationship between hospital characteristics and patient demographics with the occurrence of NBSI. Methods: This study utilized discharge data from the Healthcare Cost and Utilization Project (HCUP) Kids' Inpatient Databases (KID) for the year 2019. Bivariate and multivariate logistic regression models were employed to analyze patient-level encounters of NBSIs. The analysis examined various factors including hospital size, location, and teaching status, as well as patient-specific variables such as gender, age, race, service lines, payment sources, and major operating room procedures. Results: The results indicate that Public and Private not-for-profit hospitals showed significantly lower odds of experiencing NBSIs when compared to Private investor-owned hospitals, as did smaller, rural, and nonteaching hospitals when compared to large hospitals. Additionally, individual factors such as gender, age, race, service lines, payment sources, and types of major operating room procedures were found to have varying levels of significance in relation to NBSI. Conclusions: This study provides important insights into PAEs within the inpatient hospital setting, particularly focusing on NBSIs within the PDI framework. The findings highlight critical areas for the development of evidence-based interventions and guidelines, which are essential for clinicians and policymakers. Ultimately, this study contributes to the understanding and improvement of pediatric patient safety by emphasizing the necessity for targeted strategies to mitigate the risk of NBSI.